Khazanah Leksikon Tradisi Adat Pengangkatan Datu Rajamuda Kesultanan Sumbawa - Muhaimin, Ahmad Helmi; Aswandikari, Aswandikari; Burhanuddin, Burhanuddin; Setiawan, Irma; Sukri, Muhammad (Jayapangus Press, 2025)
Language is an essential part of cultural heritage that represents the values, knowledge, and collective identity of a society. This study aims to examine the forms and meanings of lexicons used in the coronation tradition of Datu Rajamuda in the Sultanate of Sumbawa as representations of culture, value systems, and power structures within the Samawa community. It also seeks to reveal how language functions as a medium for preserving local values and strengthening collective identity within the royal cultural context. The study employs ethnolinguistic and anthropolinguistic approaches with a descriptive qualitative method through observation, in-depth interviews, and field documentation at Bala Kuning Palace, Sumbawa. The data were analyzed interactively through stages of data reduction, presentation, and conclusion drawing to obtain a deep cultural understanding. The findings reveal 35 lexical data, consisting of 9 single-word forms and 26 phrase forms, each carrying lexical and cultural meanings. Lexicons such as kantar, badong, ai kadewa, and cilo datu rajamuda function not only as tools of communication but also as symbols embodying philosophical, moral, and spiritual values that reflect legitimacy of power and the social order of the Sultanate of Sumbawa. Each lexicon demonstrates the integration between language, custom, and value systems that have been inherited across generations. Culturally, the lexicons in the Datu Rajamuda coronation tradition reflect religious, social, and moral values such as loyalty, empathy, responsibility, and purity as the foundation of traditional leadership. This research emphasizes that language in the Samawa cultural context plays a vital role as a medium for preserving identity, social legitimacy, and character education based on local wisdom. Thus, the Datu Rajamuda coronation tradition is not merely a customary ritual but a manifestation of harmony between culture, religion, and social order that sustains the continuity and cohesion of the Samawa community amid modern changes.